PERCEPTIVE VOICE ANALYSIS IN CHILDREN WITH SPECIFIC LANGUAGE DISORDERS - Ilic Savic, Ivana (Acta medicae Medianae, 2022)
Specific language disorder (SLD) is a neurodevelopmental disorder that characterizes language deficits together with the preservation of some cognitive domains. Voice evaluation in children with SLD should indicate and encourage a new perspective and provide us with a conceptual approach that has the potential to better understand the voice system of children with SLD by completing a guide to voice rehabilitation in these children. The aim of this research was to determine the components of the voice system, voice quality, as well as potential gender differences among children with SLD. The sample included 30 children with developmental dysphasia, aged 3 to 9 years (AS = 6.40; SD = 1.714), of whom 20 were boys and 10 were girls. The adapted Quick Screen For Voice and GRBAS scale were used to assess the voice quality. The obtained results show that the largest number of children with SLD have adequate biological predispositions for typical voice quality. A large number of children with SLD have no change in all analyzed perceptual voice parameters. The most common perceptual changes in the voice have been mild, followed by moderate, and the least common have been pronounced changes in the voice. There have been significant differences in the degree of hoarseness and hoarseness of the voice in relation to gender, more pronounced in boys (p < 0.05). Although the changes in voice quality in children with SLD have been mild, they are potentially significant for vocal pathologists, pointing to the importance of prevention, which should be implemented at an early age in order to preserve a healthy and quality voice.